(untitled) (Eurasian Research Bulletin, 2023)
Periodontal diseases , being the cause of most cases of tooth loss, are a focus of chronic infection with a negative impact on the health of the body and the quality of life in general. According to the majority of researchers, the primary role in the development of periodontal pathology is assigned to the microbial factor [3,13]. The complex of periodontopathogenic bacteria that are detected in periodontitis includes such microorganisms as: Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola, Prevotella intermedia and Aggregatibacter actinomycetemcomitans [15,7]. Qualitative analysis of these pathogens is particularly important both for diagnosis and for assessing the risk of developing the disease. The most specific and highly sensitive method shown for this study is PCR (polymerase chain reaction).